(3JGQjN GdESdGe hWHbGJ GdeTGgjQ hGdCYdGes - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s ((3YHOGdNGdb GdbGSej s)
(3ChdgG (B:s
(3JQLeI CMeO Hf EHQGgje Hf CMeO Hf CHj GdYHGS Hf GdNWGH GdQGRj ef GdWHbI GdNeSjf (B((3SfI EMOi hJSYjf hCQHYeGFI s
(3BNQgG (B:s
(3JQLeI jMji Hf eMeO Hf CMeO GdeMGedj SeY efg CHhehSi GdeOjfj hZjQg BNQ GdeLdO, hGdMeO ddg s
(3GfXQ Qbe (B98 (3, Qbe (B596 (3, Qbe (B949 (3JGQjNs
(3fSNI JGSYI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B46 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B74 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs